Case Report: Auditory Hallucination Induced by Amitriptyline for the Treatment of Atypical Odontalgia - Watanabe, Motoko; Nakabayashi, Tetsuo; Nayanar, Gayatri; Takao, Chihiro; Maeda, Chizuko; Tu, Trang Thi Huyen; Motomura, Haruhiko; Toyofuku, Akira (Frontiers in Psychiatry, 2022)
Although auditory hallucination is often associated with psychiatric diseases and organic brain illness, it is rarely an adverse effect of antidepressants. Amitriptyline is considered one of the first-line medications for the psychopharmacotherapy of chronic pain, including atypical odontalgia (AO), which presents as chronic tooth pain without corresponding abnormalities. This is the first case report about a patient with AO who experienced auditory hallucination following the administration of low-dose amitriptyline. A 43-year-old female complained of chronic toothache following dental procedures, diagnosed as AO. Amitriptyline was administered at an initial dose of 25 mg once daily and gradually increased up to 60 mg with improved AO symptoms in 7 months. The dose of amitriptyline was then decreased to a continuation dose of 30 mg. In 24 months, the AO symptoms remarkably improved; however, she reported that she had been hearing voices at midnight for the past year. An adverse effect of amitriptyline was suspected since she did not have a history of psychotic symptoms. The amitriptyline dose was decreased and continued at 25 mg. Magnetic resonance imaging and psychiatric consultation revealed no brain or psychiatric abnormalities. Following final prosthodontic treatment, the amitriptyline was discontinued in 30 months. Two months after the discontinuation, the auditory hallucinations had almost disappeared with no recurrence of AO. This case report suggests that amitriptyline could induce auditory hallucination even in conventional doses throughout the treatment of chronic pain, including AO.